Identifikasi Nilai dan Unsur Dakwah di Lingkungan Pondok Pesantren Al Khairot Malang - Yuliana Cita Siti Hijria (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2022)
Djumransjah and Abdul Malik Karim Amrullah explained that Islamic education is a component that cannot be separated from one another, because it always gives warnings if there are symptoms of division and violations of religious teachings, by inviting and calling on people to do good, telling people to do good deeds. ma'ruf and prevent the evil. The method taken is to make people aware that good deeds will bring profit and happiness both in this world and in the hereafter. And this is what is practiced by Islamic boarding schools as a means of educators. Has its own da'wah to students and students who study and live in it. In this study, we will discuss in depth how and to what extent the identification of system values ​​and elements of da'wah in accordance with the adolescent stage to santri and female students of Al-Khoirot Islamic boarding school Malang. The approach that the researcher uses in this research is a qualitative approach and the type of research used is descriptive or by using a descriptive analytic approach. So the conclusion after doing direct identification by matching the existing system at Pondok Pesantren Al-Khoirat Malang. It can be concluded that with the Mau'idhah Hasanah carried out by Ustadz and Ustadzah which ultimately made the students' and women's personalities better.